g-acceleration of gravity: its measurement from the shape of water by using a computerized rotational system - Pintao, Carlos A. F.; Souza Filho, Moacir Pereira de [UNESP] (Iop Publishing Ltd, 2007)
This paper proposes a different experimental setup compared with the traditional ones, in order to determine the acceleration of gravity, which is carried out by using a fluid at a constant rotation. A computerized rotational system-by using a data acquisition system with specific software, a power amplifier and a rotary motion sensor-is employed in order to evaluate the angular velocity and g. An equation to determine g is inferred from fluid mechanics. For this purpose, the fluid's parabolic shape inside a cylindrical receptacle is considered using a rotational movement.